2020
DOI: 10.3389/fcell.2020.615671
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lncRNA-mRNA Regulatory Module to Explore the Pathogenesis and Prognosis of Melanoma

Abstract: Skin cutaneous melanoma (SKCM) is an aggressive form of skin cancer that results in high mortality rate worldwide. It is vital to discover effective prognostic biomarkers and therapeutic targets for the treatment of melanoma. Long non-coding RNA (lncRNA) has been verified to play an essential role in the regulation of gene expression in diseases and tumors. Therefore, it is significant to explore the function of lncRNAs in the development and progression of SKCM. In this paper, a set of differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 66 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…Based on the PPI network, the MCODE algorithm was used to cluster the network into important modules and then the cytoHubba tool was used to calculate the degree value of each node. In line with the previous research, only the nodes with a degree value > 20 were considered as hub mRNAs (21).…”
Section: Additional Ltering Of Mrnas and Lncrnasmentioning
confidence: 69%
See 1 more Smart Citation
“…Based on the PPI network, the MCODE algorithm was used to cluster the network into important modules and then the cytoHubba tool was used to calculate the degree value of each node. In line with the previous research, only the nodes with a degree value > 20 were considered as hub mRNAs (21).…”
Section: Additional Ltering Of Mrnas and Lncrnasmentioning
confidence: 69%
“…The LUAD cell line A549 and all compounds in the database were chosen for this analysis, and a list of compounds with connectivity scores ranging from -100 to 100 was obtained. In brief, a positive score indicates the similarity between a compound's signature and the signature of the query, while a negative score indicates that the two signatures are opposing (21,34). The magnitude of the score corresponds to the magnitude of similarity or dissimilarity.…”
Section: Connectivity Map-based Drug Screening and Molecular Dockingmentioning
confidence: 99%
“…As precision medicine becomes increasingly relevant in healthcare, the field of pharmacogenomic also continues to gain prominence in the clinical setting [ 50 ]. Meanwhile, multiple studies have demonstrated that small molecule drugs can modify lncRNA expression, which suggests a promising therapy for human diseases [ 51 , 52 ]. Thus, based on the hypo-EMTRN and the information in D-lnc, we inferred that some potential drugs could be used for the treatment of GBM patients by constructing the drug-target association network targeting lncRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the three datasets were listed in Table 1. The differential expression analysis by integration of TCGA and GTEx datasets, and identi cation of the differentially expressed genes (DEGs) between melanoma and normal samples was conducted as described in our previous study [19].…”
Section: Gene Expressions and Differential Expression Analysismentioning
confidence: 99%